Repair Technique for Fractured Implant-Supported Metal-Ceramic Restorations: A Clinical Report - Wady, Amanda Fucci [UNESP]; Paleari, Andre Gustavo [UNESP]; Queiroz, Thallita Pereira; Margonar, Rogerio (Allen Press Inc, 2014)
The fracture of porcelain structures have been related in either natural dentition or implant-supported restorations. Techniques using a composite resin or indirect methods can be used. This article presents a porcelain fracture on implant-supported metal-ceramic restoration. IPS Empress e.max laminate veneer restoration was used to repair the fracture. With this technique, it was possible to restore aesthetics and function, combined with low cost and patient satisfaction.
Keywords: fracture; ceramics; repair; laminate veneer; implantology